Die soziale Struktur von Alalaḫ und Ugarit (V). Die Weingärten des Gebietes von Alalaḫ im 15. Jahrhundert - Dietrich, M.
I = WO 3 (1966) 188-205; II = WO 5 (1969) 54-93; III in Vorbereitung; IV = ZA 60 (1970).